2019
DOI: 10.3390/app9183882
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of In-Plane Displacement in Two Orthogonal Directions by Digital Speckle Pattern Interferometry

Abstract: The measurement of in-plane displacement in two orthogonal directions is of considerable significance for modern industries. This paper reports on a spatial carrier phase-shift digital speckle pattern interferometry (DSPI) for the simultaneous measurement of in-plane displacement in two orthogonal directions. The object is illuminated from a single direction and observed from four symmetrical directions simultaneously. One pair of the four observation directions is sensitive to in-plane displacement in one dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Yan et al 12 reported the measurement of planar displacement in two orthogonal directions using DSPI with a spatial phase shift. In this case, a combination of four apertures is used where each of them coincides with the surface of a four-sided mirror that deflects the observation point.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yan et al 12 reported the measurement of planar displacement in two orthogonal directions using DSPI with a spatial phase shift. In this case, a combination of four apertures is used where each of them coincides with the surface of a four-sided mirror that deflects the observation point.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al 12 . reported the measurement of planar displacement in two orthogonal directions using DSPI with a spatial phase shift.…”
Section: Introductionmentioning
confidence: 99%